PENINGKATAN KEMAMPUAN MOTORIK KASAR MELALUI SENAM IRAMA CERIA PADA ANAK TUNAGRAHITA RINGAN - NURDANINGSIH, SITI (Jurnal Pendidikan Khusus, 2018)
Abstract. The mild mentally retardation children in gross motoric got disturbance, this was caused by the limitedness of ability or intelligence and also less concentration. To handle the mild mentally retardation in gross motoric things it could be used a way i.e. managing the body through doing sport in the form of cheerful rhythm gymnastic. This research had purpose to describe the enhancement of gross motoric ability of class III mild mentally retardation children in SLB Aisyiyah Tulangan through cheerful rhythm gymnastic i.e. they could do the cheerful rhythm gymnastic correctly. This research was a class treatment research which was implemented in 2 cycles and each cycle was done in 2 meetings. The subject of this research was mild mentally retardation children of class III in SLB Aisyiyah Tulangan Sidoarjo. The method of this research was descriptive qualitative and the data collection technique used observation and documentation. The research success criterion was stated success if the value had reached minimum 75%. The research result was there was enhancement of gross motoric ability from pre cycle i.e. 37,7%, cycle I became 57,2% while cycle II became 80%. Based on the explanation above, it could be concluded that cheerful rhythm gymnastic could enhance the gross motoric ability of class III mild mentally retardation children in SLB Aisyiyah Tulangan Sidoarjo.         Keywords : Gross motoric, cheerful rhythm gymnastic.